Diary of a physician in California; being the results of actual experience, including notes of the journey by land and water, and observations on the climate, soil, resources of the country, etc. - Tyson, James L. (James Lawrence); YA Pamphlet Collection (Library of Congress) (New York, D. Appleton & company; Philadelphia, G.S. Appleton, 1850)
Dr. James L. Tyson sailed from Baltimore for California in January 1849, crossing the Isthmus and sailing on to San Francisco. Diary of a physician in California (1850) recounts his 1849 tour of the Northern Mines in search of a likely place for his medical practice and his hospital at Cold Spring, where his patients included a number of Oregonians. Tyson closes his hospital at the end of the summer, sailing from San Francisco as a ship's physician, crossing the Isthmus and landing in the United States in December 1849. His diary pays special attention to miners' health and working conditions.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; California -- Gold discoveries; Voyages to the Pacific coast; Ethnic groups -- California